Magic and Christianity: An Exegesis on Magical Passages in the Acts of the Apostles - Chandra Han (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Magic is a significant theme in The Acts of the Apostle but is undermined by scholars. The significance of this theme is obvious in the so-called five episodes or passage of magic. Thus, how does Christian understand of magic particularly in the Acts of the Apostles is also prominent. This article aimed to re-examine all five episodes of magic in The Acts of the Apostles that Christian may have a more comprehensive understanding of magic and able to conquer the reality of magic which is still very relevant in our contemporary ministry in Indonesia. The method of this article was literature study. By the study it was concluded that the magic in Acts is best understood to further its apologetical purpose, because the passages clearly demonstrate evil as the reality behind magic, thus the confrontation between God’s power and magic is inevitable for it is between God and evil.